PKM. PEMBERIAN REINFORCEMENT DALAM PEMBELAJARAN DAN PERKEMBANGAN MORAL ANAK DI PAUD III SARASWATI DENPASAR - I Putu Karpika; Luh Putu Swandewi Antari; I Made Surat; Ni Made Pira Erawati (LP3M Universitas PGRI Mahadewa Indonesia, 2023)
This PKM is motivated by the absence of a real solution regarding providing reinforcement at PAUD III Saraswati Denpasar school. This service aims to provide a solution for how to provide reinforcement for the moral development of early childhood in preschool education. The methods used are socialization and mentoring. In the implementation of the 1st and 2nd stages of PKM socialization, much progress has been achieved. Data was obtained through free interviews, observation and documentation. Data sources were obtained through school principals, class teachers who functioned as informants. The results of the service found included: In learning aspects of moral development, there were several reinforcements provided by other educators/teachers at PAUD III Saraswati Denpasar, namely: the use of positive reinforcement and the use of negative reinforcement. Learning aspects of moral development at PAUD III Saraswati Denpasar is carried out through all activities including: habituation, singing songs, shouting moral messages, stories, and so on. The impact that occurs after reinforcement is given to children is: positive reinforcement includes: children become happy, enthusiastic about following lessons. Meanwhile, negative reinforcement includes: not repeating bad actions. Providing reinforcement can improve the moral development of early childhood because after being given reinforcement, children who have good moral development increasingly increase their moral development, while children who have less moral development gradually experience positive development over time after being given continuous negative reinforcement.